The Non-Hemostatic Aspects of Transfused Platelets - Sut, Caroline; Tariket, Sofiane; Aubron, Cécile; Aloui, Chaker; Hamzeh-Cognasse, Hind; Berthelot, Philippe; Laradi, Sandrine; Greinacher, Andreas; Garraud, Olivier; Cognasse, Fabrice (Frontiers in Medicine, 2018)
Platelets transfusion is a safe process, but during or after the process the recipient may experience an adverse reaction and occasionally a serious adverse reaction (SAR). In this review, we focus on the inflammatory potential of platelet components and their involvement in SARs. Recent evidence has highlighted a central role for platelets in the host inflammatory and immune responses. Blood platelets are involved in inflammation and various other aspects of innate immunity through the release of a plethora of immunomodulatory cytokines, chemokines and associated molecules, collectively termed biological response modifiers (BRMs) that behave like ligands for endothelial and leukocyte receptors and for platelets themselves. The involvement of platelet components in SARs – particularly on a critically ill patient’s context - could be related, at least in part, to the inflammatory functions of platelets, acquired during storage lesions. Moreover, we focus on causal link between platelet activation and immune-mediated disorders (Transfusion-Associated Immunomodulation, Platelets, Polyanions and Bacterial Defense and Alloimmunization). This is linked to the platelets’ propensity to be activated even in the absence of deliberate stimuli and to the occurrence of time-dependent storage lesions.